The integration of stock exchanges: The case of the Latin American Integrated Market (MILA) and its impact on ownership and internationalization status in Colombian brokerage firms - Yepes Rios, Beatriz (2015)
This paper describes the changes in ownership and internationalization of the brokerage firms in Colombia as a result of the regional integration process of its stock exchange market through the Latin AmericanIntegrated Market (MILA). It proposes that the integration of stock exchanges generated transformations within the brokerage sector, and affected companies in response pursue different strategies toremain competitive in the current state of affairs. In the case of Colombia, stock exchange integration through MILA has resulted into mergers between local brokerage firms, acquisitions from both national and international companies and changes in ownership.